2016
DOI: 10.11124/jbisrir-2016-002499
|View full text |Cite
|
Sign up to set email alerts
|

Interventions incorporating physical and cognitive elements to reduce falls risk in cognitively impaired older adults

Abstract: Overall, multicomponent interventions incorporating both physical and cognitive components demonstrated positive effects on balance, functional mobility and gait speed when compared with a control and had significantly better effect on balance and gait speed within mild cognitive impairment populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 47 publications
0
17
0
1
Order By: Relevance
“…This implies that involvement in an exercise program with cognitive training or participation in cognitive training alone is much better than just doing daily activities in enhancing functional mobility. 25 This could be due to crossmodality transfer wherein training cognitive functions can influence the performance of physical functions. 26 The lack of significant difference between groups in the outcome measures may also be due to the high percentage of participants in each intervention group with less than the expected duration of participation.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that involvement in an exercise program with cognitive training or participation in cognitive training alone is much better than just doing daily activities in enhancing functional mobility. 25 This could be due to crossmodality transfer wherein training cognitive functions can influence the performance of physical functions. 26 The lack of significant difference between groups in the outcome measures may also be due to the high percentage of participants in each intervention group with less than the expected duration of participation.…”
Section: Discussionmentioning
confidence: 99%
“…There Is a growing interest in merging physical and cognitive stimulation (mind-body exercise), such as TC and Yoga, in health promotion in aging individuals (Ni et al, 2014;Gothe et al, 2016;Marmeleira et al, 2018). Furthermore, a recent systematic review suggested that interventions incorporating both physical and cognitive components not only benefit cognitive function, but also physical functions, including balance (Booth et al, 2016). In the present study the association of cognitive function with balance through a TC intervention program Is comparable to a cross-sectional study (Leandri et al, 2015) that evaluated cognitive function using MoCA and static balance with participants eyes closed (similar to the present study).…”
Section: Discussionmentioning
confidence: 99%
“…For example, treatment implications would differ if the effects of physical activity and diet were found to act through aerobic fitness and inflammation, respectively, instead of both contributing to improved metabolic function. In contrast, finding synergistic effects might suggest that multicomponent interventions with both exercise and dietary components may be necessary to achieve ADRD risk reduction [129,[341][342][343][344]. Nevertheless, the present literature base suggests several important themes that may help to further optimize lifestyle approaches to ADRD prevention.…”
Section: Neurogenesis / Synaptogenesismentioning
confidence: 99%